Optimal climate for large trees at high elevations drives patterns of biomass in remote forests of Papua New Guinea. (31st May 2017) - Venter, Michelle; Dwyer, John; Dieleman, Wouter; Ramachandra, Anurag; Gillieson, David; Laurance, Susan; Cernusak, Lucas A.; Beehler, Bruce; Jensen, Rigel; Bird, Michael I.
Abstract: Our ability to model global carbon fluxes depends on understanding how terrestrial carbon stocks respond to varying environmental conditions. Tropical forests contain the bulk of the biosphere's carbon. However, there is a lack of consensus as to how gradients in environmental conditions affect tropical forest carbon. Papua New Guinea (PNG) lies within one of the largest areas of contiguous tropical forest and is characterized by environmental gradients driven by altitude; yet, the region has been grossly understudied. Here, we present the first field assessment of aboveground biomass (AGB) across three main forest types of PNG using 193 plots stratified across 3, 100‐m elevation gradient. Unexpectedly, AGB had no direct relationship to rainfall, temperature, soil, or topography. Instead, natural disturbances explained most variation in AGB. While large trees (diameter at breast height > 50 cm) drove altitudinal patterns of AGB, resulting in a major peak in AGB (2, 200–3, 100 m) and some of the most carbon‐rich forests at these altitudes anywhere. Large trees were correlated to a set of climatic variables following a hump‐shaped curve. The set of "optimal" climatic conditions found in montane cloud forests is similar to that of maritime temperate areas that harbor the largest trees in the world: high ratio of precipitation to evapotranspiration (2.8), moderate mean annual temperature (13.7°C), and low intra‐annual temperature range (7.5°C). At extreme altitudes (2, 800–3, 100 m), where tree diversity elsewhere is usually low and large trees are generally rare or absent, specimens from 18 families had girths >70 cm diameter and maximum heights 20–41 m. These findings indicate that simple AGB‐climate‐edaphic models may not be suitable for estimating carbon storage in forests where optimal climate niches exist. Our study, conducted in a very remote area, suggests that tropical montane forests may contain greater AGB than previously thought and the importance of securing their future under a changing climate is therefore enhanced. Abstract : Montane cloud forests are often thought to be squat and gnarly with little carbon benefit, a misconception we show in this study. Optimal climate conditionsfor large trees drive forest biomass patterns along a 3000m elevation gradient in Papua New Guinea. These optimal climate niches, similar to those also found in the temperate coastal climates that are home to the largest trees in the world, are also found at high elevations in remote tropical forests of Papua New Guinea.